PERAN ETIKA KEPRIBADIAN DAN KODE ETIK GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Silvia Neltiana; Rahmi Putri (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2025)
The teacher code of ethics is an important guideline in carrying out professional duties as an educator. This article discusses in depth the principles of the teacher code of ethics, its role in education, and its implications for the quality of learning. This research aims to analyse how the implementation of the teacher code of ethics can improve professionalism and the relationship between educators and students, parents, and the community. The research method used is a literature review that refers to various literature and regulations related to the teacher code of ethics. In addition, the impact of compliance and violation of the code of ethics in educational practice was analysed. The results show that a good understanding and implementation of the code of ethics can improve the integrity, responsibility, and quality of learning provided by teachers. Conversely, violations of the code of ethics can reduce public trust in the teaching profession and hinder the effectiveness of the teaching and learning process. This research emphasises the importance of continuous training and socialisation of the teachers' code of ethics to maintain the values of professionalism. Thus, the teacher code of ethics is not only a written rule, but also a foundation in building an ethical, professional and quality educational environment.